Isolation of phosphate solubilizing fungus from rice fields of Odisha for agro‐ecological sustainable agriculture. Issue 2 (12th August 2022) - Krishna Samal, D P; Sukla, Lala Behari
Abstract: Phosphorus (P), the second most essential nutrient, plays a remarkable role in energy transfer, storage, plant growth, and development. It is the least mobile and accessible to plants in most soil conditions as compared to the other key nutrients. Phosphate‐solubilizing fungus (PSF) plays a vital role in supplying phosphorous to plants from the soil. Hence this research intends to assess the phosphorous and nutritional status of collected soil samples as well as isolation of potential fungal strains. Twelve soil samples were taken from three costal districts of Odisha (Bhadrak, Jajpur, and Balasore). All six key soil parameters like pH, electrical conductivity, organic carbon, nitrogen, phosphorous, and potassium were examined for correlation and found to be significantly associated with each other. Fungal colonies were enumerated, grown and pure colonies were found. A total of four potential fungal strains were isolated, screened from rhizospheric soil and evaluated for their phosphate solubilization efficiency on Pikovskaya's agar selective media. They produce the halo zones around their colony approximately 3.3 cm (PRF2), 2.96(PRF3), and 3.06(PRF4) cm within 10 days of incubation. Aspergillus niger was a highly efficient strain in solubilizing phosphate with the solubilization index (SI) of 3.56 cm and also showed the greatest drop in pH in the PVK broth containing rock phosphate.